2009
DOI: 10.1111/j.1365-2826.2008.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Forms of Oestrogen Rapidly Upregulate Cell Proliferation in the Dentate Gyrus of Adult Female Rats

Abstract: Oestrogens are known to exert significant structural and functional effects in the hippocampus of adult rodents. The dentate gyrus of the hippocampus retains the ability to produce neurones throughout adulthood and 17beta-oestradiol has been shown to influence hippocampal neurogenesis in adult female rats. The effects of other oestrogens, such as oestrone and 17alpha-oestradiol, on neurogenesis have not been investigated. The present study aimed to investigate the effects of 17beta-oestradiol, oestradiol benzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 76 publications
5
123
0
2
Order By: Relevance
“…The meaning of these observations is still subject to speculation, but growing evidence now suggests that production of estrogens by radial glial cells could be important in the context of embryonic or adult neurogenesis (Garcia-Segura et al, 2001; Martinez- Cerdeno et al, 2006;Galea, 2008;Barha et al, 2009;De Nicola et al, 2009;Mouriec et al, 2009). In addition, there is substantial evidence in fish showing that cyp19a1b expression is strongly up-regulated by estrogens and aromatizable androgens Halm et al, 2002;Menuet et al, 2005;Le Page et al, 2006, 2008Mouriec et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meaning of these observations is still subject to speculation, but growing evidence now suggests that production of estrogens by radial glial cells could be important in the context of embryonic or adult neurogenesis (Garcia-Segura et al, 2001; Martinez- Cerdeno et al, 2006;Galea, 2008;Barha et al, 2009;De Nicola et al, 2009;Mouriec et al, 2009). In addition, there is substantial evidence in fish showing that cyp19a1b expression is strongly up-regulated by estrogens and aromatizable androgens Halm et al, 2002;Menuet et al, 2005;Le Page et al, 2006, 2008Mouriec et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In other vertebrates, including teleost fish, radial cells persit in adult (Onteniente et al, 1983;Menuet et al, 2003Menuet et al, , 2005Zupanc and Clint, 2003;Pellegrini et al, 2007) and it was recently shown that radial cell can generate neurons throughout adult life in fish Adolf et al, 2006). The role of aromatase in radial glial cells is poorly understood, but estrogens are now strongly suspected to participate in the process of embryonic, adult or reparative neurogenesis (Garacia-Segura et al, 2001;Martinez-Cerdeno et al, 2006;Galea, 2008;Mouriec et al, 2008;Barha et al, 2009;De Nicola et al, 2009;Kimmel et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Given that ERs in the brain show tissue and region-specific patterns of expression (Shughrue et al, 1997), and the diverse behaviors they regulate (Kudwa et al, 2006;Rhodes and Frye, 2006), it is plausible that different forms of estrogen could have profound and distinct effects on neural plasticity and/or behavior. Despite the fact that estrone is centrally active (Barha et al, 2009) and is the main component of the HRT Premarin, to our knowledge only one study has directly examined the effects of estrone on learning (Farr et al, 2000). Thus, in this study we sought to determine whether there were differential effects of the estrogens, estradiol, and estrone, on contextual fear conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…These doses were chosen based on earlier studies investigating spatial learning and hippocampal neurogenesis (Tanapat et al, 1999;Ormerod et al, 2003;Holmes et al, 2002;Tanapat et al, 2005;Barha et al, 2009). A high dose of 10 mg 17b-estradiol was chosen because it results in circulating levels of estradiol observed on the morning of proestrus (Viau and Meaney, 1991) and has been shown to enhance cell proliferation 30 min (Barha et al, 2009), 2 h (Tanapat et al, 1999;Tanapat et al, 2005), and 4 h (Ormerod et al, 2003;Barha et al, 2009) after injection. However, this same dose produces supraphysiological levels of estradiol shortly after administration (Woolley and McEwen, 1993).…”
Section: Drug Treatmentmentioning
confidence: 99%
See 1 more Smart Citation